An Interventional Magnetic Resonance Imaging Technique for the Molecular Characterization of Intraprostatic Dynamic Contrast Enhancement - Cynthia Ménard; Robert C. Susil; Peter Choyke; Jonathan Coleman; Robert Grubb; Ahmed Gharib; Axel Krieger; Peter Guion; David Thomasson; Karen Ullman; Sandeep Gupta; Virginia Espina; et al. (Molecular Imaging)
The biological characterization of an individual patient's tumor by noninvasive imaging will have an important role in cancer care and clinical research if the molecular processes that underlie the image data are known. Spatial heterogeneity in the dynamics of magnetic resonance imaging contrast enhancement (DCE-MRI) is hypothesized to reflect variations in tumor angiogenesis. Here we demonstrate the feasibility of precisely colocalizing DCE-MRI data with the genomic and proteomic profiles of underlying biopsy tissue using a novel MRI-guided biopsy technique in patients with prostate cancer.